2016
DOI: 10.1186/s13041-016-0219-1
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in hypothalamic Gfap expression, glial cells and α-tanycytes in lean and hypermetabolic Gnasxl-deficient mice

Abstract: BackgroundNeuronal and glial differentiation in the murine hypothalamus is not complete at birth, but continues over the first two weeks postnatally. Nutritional status and Leptin deficiency can influence the maturation of neuronal projections and glial patterns, and hypothalamic gliosis occurs in mouse models of obesity. Gnasxl constitutes an alternative transcript of the genomically imprinted Gnas locus and encodes a variant of the signalling protein Gαs, termed XLαs, which is expressed in defined areas of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Meanwhile, the expression levels of IR mRNA in the isolated nonastrocyte cells (tdTomato − APC − ) from IRKO GFAP mice were comparable to the IR loxp group, confirming the specificity of the deletion (Fig 1C). Previous studies have suggested that tanycytes near the third ventricle express GFAP [30]. Therefore, to further verify the purity of astrocytic FACS isolation, we measured gene expression of different markers of neuronal, tanycytic, microglia, and endothelial markers and confirmed the specific isolation of astrocytes via FACS (S3 Fig).…”
Section: Resultssupporting
confidence: 54%
“…Meanwhile, the expression levels of IR mRNA in the isolated nonastrocyte cells (tdTomato − APC − ) from IRKO GFAP mice were comparable to the IR loxp group, confirming the specificity of the deletion (Fig 1C). Previous studies have suggested that tanycytes near the third ventricle express GFAP [30]. Therefore, to further verify the purity of astrocytic FACS isolation, we measured gene expression of different markers of neuronal, tanycytic, microglia, and endothelial markers and confirmed the specific isolation of astrocytes via FACS (S3 Fig).…”
Section: Resultssupporting
confidence: 54%
“…However, although vimentin compensated for most cells, no phenotype was observed. Therefore, we indicated the GFAP specific phenotype for the auricular chondrocytes, although these phenotypes of GFAP are not compensated by vimentin (Holmes et al, ). Meanwhile, one of the GFAP phenotypes was multinucleation.…”
Section: Discussionmentioning
confidence: 76%
“…For example, conditional knockout of the DNA methyltransferase, DNMT1 (M54), in the mouse brain ( Narayanan et al, 2014 ) activates a set of DEGs that significantly overlapped (p adj = 1.4 × 10 −11 ) with a human module, IFGblue, enriched for unfolded protein response and DNA repair pathway genes. In another example, brain RNA-seq from a Gnasxl -deficient mouse ( Holmes et al, 2016 ) (M156) overlapped with FPbrown, a coexpression module (p adj = 5.4 × 10 −9 ) enriched for genes involved in oxidative phosphorylation and mitochondrial translation. Interestingly, Gnas , which encodes a G-protein alpha stimulatory subunit, is a complex, imprinted genomic locus implicated in hypothalamic control of energy balance.…”
Section: Resultsmentioning
confidence: 99%
“…Other manipulations generate signatures similar to AD models, including PTCH1 knockout (M183) ( Ung et al, 2018 ), nmf205 (M182) ( Ishimura et al, 2016 ), and neuroserpin mutant (M205) ( Guadagno et al, 2017 ). Modules poorly enriched for cell type signatures (asterisk, right) show selected overlaps with FTD-ALS models (M28, M43; Ibrahim et al, 2013 , and Lagier-Tourenne et al, 2013 , respectively) and other, unexpected genetic manipulations (M158, M111, M54, and M156; Vied et al, 2016 , Maze et al, 2015 , Narayanan et al, 2014 , and Holmes et al, 2016 , respectively). See Tables S5 and S6 for comprehensive results, including sample sizes for all comparisons.…”
Section: Figurementioning
confidence: 99%